Low-latitude Holocene hydroclimate derived from lake sediment flux and geochemistry - Parker, Adrian G.; Preston, Gareth W.; Parton, Ash; Walkington, Helen; Jardine, Phillip E.; Leng, Melanie J.; Hodson, Martin J. (Wiley, 2016)
This study investigates hydrological responses to climatic shifts using sediment flux data derived from two dated palaeolake records in south-east Arabia. Flux values are generally low during the early Holocene humid period (EHHP) (∼9.0–6.4k cal a BP) although several short-lived pulses of increased detrital input are recorded, the most prominent of which is dated between ∼8.3 and 7.9k cal a BP. The EHHP is separated from the mid-Holocene humid period (MHHP) (∼5.0–4.3k cal a BP) by a phase of increased sediment flux and aridity, which began between ∼6.4 and 5.9k cal a BP and peaked between ∼5.2 and 5.0k cal a BP. The termination of the MHHP is marked by a phase of high detrital sediment flux between ∼4.3 and 3.9k cal a BP. While long-term shifts in climate are most likely linked to changes in the summer position of the Intertropical Convergence Zone and associated Indian and African monsoon systems, it is noted that the abrupt, short-term phases of aridity observed in both records are coeval with intervals of rapid climate change globally, which triggered non-linear, widespread landscape reconfigurations throughout south-east Arabia.